Associação Nossa Senhora das Candeias : maternagem e movimento de mulheres pretas (1980-2004) - Silva, Naiane Rodrigues da (2019)
This dissertation presents the results of a research on the movement of black women rural workers in the city of Feira de Santana from 1987 to 2002. The research aims to identify how the experiences of women living in Lagoa Salgada were guided by mothering and led them to develop a political struggle that culminates in the creation of Nossa Senhora das Candeias Association. To this, I develop an analysis on the construction of belonging with the community, on empowerment believing that the main motivation for the development of the movement was mothering. The research seeks to identify how women make their private life a collective struggle in the public sphere, developing not only themselves but the community in which they belong.